Arran pitchstone (Scottish volcanic glass): New dating evidence - Ballin, Torben Bjarke (Journal of Lithic Studies, 2015)
In the present paper, the author offers new absolute and contextual dating evidence for Scottish archaeological pitchstone. Much archaeological pitchstone from the Scottish mainland is recovered from unsealed contexts of multi-period or palimpsest sites, and pitchstone artefacts from radiocarbon-dated pits therefore provide important dating evidence for this material group and its associated exchange network. In Scotland, all archaeological pitchstone derives from outcrops on the Isle of Arran, in the Firth of Clyde, and on the source island pitchstone-bearing assemblages include diagnostic types from the Mesolithic, Neolithic and Early Bronze Age period. Off Arran, pitchstone-bearing assemblages never include Mesolithic types, such as microliths, suggesting a post Mesolithic date. This suggestion is supported by worked pitchstone from radiocarbon-dated pits, where all presently available dates indicate that, on the Scottish mainland, Arran pitchstone was traded and used after the Mesolithic period, and in particular during the Early Neolithic period.